PENGEMBANGAN KARAKTERISTIK OPTIS PADA LARUTAN PERAK KOLOID MENGGUNAKAN METODE ELEKTRO-OPTIS - Tiwiyaningsih, Tiwiyaningsih; Rahmawati, Aidah; Nurhasanah, Wahidatun Dewi; Richardina, Very; Khumaeni, Ali; Firdausi, Ketut Sofjan; Sugito, Heri; Soesanto, Qidir Maulana Binu; Azam, Much (BERKALA FISIKA, 2020)
In this paper we present a new development of optical properties on colloidal silver solutions using electro-optics effect. Samples of silver nanoparticles (NPP) were obtained by ablation method and then diluted in water to obtain various concentrations. To obtain optical characteristics of colloidal silver solutions through the electro-optical effect, the changes in the polarization of light was measured as the sample was applied by high external potential difference. The light source used was laser pointer with ï¬ = 650 nm. The results show that the colloidal silver solution shows non-linear active optical properties with increasing concentration and at a concentration of 4.6 ppm maximum natural polarization occurs. In the case of electro-optics, a voltage increase results in electro-optical contributions which correspond to the effects of non-linear polarization due to high electric fields. However, at 8 kV the maximum polarization appears also at a concentration of 4.6 ppm, which is the same as the natural polarization at that concentration. The study of colloidal silver solutions is very interesting to be further developed by electro-optical methods, because challenges and unanswered phenomena can contribute or alternative perspectives in understanding the interaction of light with matter, especially colloidal silver solutions, and the like.